Integrin GPIIIa49-57 is the pivotal switch controlling platelet fragmentation. (3rd October 2015) - Zhou, Yuwei; Jing, Fang; Shen, Ning; Liu, Min; Wang, Jing; Hong, Tao; Dang, Suying; Zhang, Wei
Abstract: Unique autologous antibodies (Abs) against platelet integrin GPIIIa49-66 (CAPESIEFPVSEARVLED) have been detected in patients with HIV-1 immune-related thrombocytopenia (HIV-1-ITP), which is capable of inducing complement-independent platelet fragmentation through reactive oxygen species (ROS) release. However, the efficiency of inducing platelet fragmentation is inconsistent among the different patient Abs or similar rabbit polyclonal Abs against the region and the reason remains unclear. In this study, we developed a batch of murine monoclonal antibodies (mAbs) against different locus of GPIIIa49-66 region by hybridoma technology. All these mAbs are capable of binding to human platelets. Among these mAbs, clones 1E7 and 5A10 were identified to target the epitope of GPIIIa49-57 (CAPESIEFP, named P1); clones 1C1 and 1E5 target GPIIIa57-64 (PVSEARVL, named P2), and clones 4D5 and 5F8 target GPIIIa59-66 (SEARVLED, named P3). By incubation of human platelets with these mAbs, the platelet fragmentation induced by mAbs against P1 was 5–6 folds higher than that by the control mAb (6-fold for 5A10 and 5.6-fold for 1E7). However, platelet fragmentation induced by mAbs against P2 (1C1) and P3 (5F8) was only 1.9- and 1.1-fold higher than that by the control mAb, respectively. Thus, our data demonstrate that platelet integrin GPIIIa49-57 is the pivotal switch controlling platelet fragmentation.